2017
DOI: 10.1039/c7ra08637g
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of glycals into vicinal-1,2-diazides and 1,2-(or 2,1)-azidoacetates using hypervalent iodine reagents and Me3SiN3. Application in the synthesis of N-glycopeptides, pseudo-trisaccharides and an iminosugar

Abstract: Glycals were found to react with a reagent system comprising of phenyliodine bis(trifluoroacetate) (PIFA) and Me 3 SiN 3 in the presence of TMSOTf as a catalyst to form the corresponding vicinal 1,2-diazides. On the other hand, they reacted with another reagent system phenyliodine diacetate (PIDA) and Me 3 SiN 3 , also in the presence of TMSOTf as a catalyst, to lead to the corresponding vicinal 1,2-azidoacetates. These azido derivatives were converted into a number of 2-azido-N-glycopeptides, pseudotrisacchar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
35
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 84 publications
1
35
0
Order By: Relevance
“…In our studies, the formation of a small amount (∼5%) of the corresponding 2,3-dihydro-4 H -pyran-4-one was observed from C3-OBn- and C3-OTBDMS-protected glycals during their reaction with the PIFA–Me 3 SiN 3 –TEMPO–H 2 O–Bu 4 NHSO 4 reagent system in CH 2 Cl 2 . Intrigued by these results and in continuation of our efforts for the functionalization of glycals, we considered it worth developing reaction conditions that could lead to higher yields of such enones. Herein, we report our findings for efficient and mild reaction conditions for the oxidation of 3- O -benzylated (as well as 3- O -silylated) glycals to the corresponding 2,3-dihydro-4 H -pyran-4-ones using PIFA–water as an oxidizing reagent system along with TEMPO as a catalyst.…”
mentioning
confidence: 87%
“…In our studies, the formation of a small amount (∼5%) of the corresponding 2,3-dihydro-4 H -pyran-4-one was observed from C3-OBn- and C3-OTBDMS-protected glycals during their reaction with the PIFA–Me 3 SiN 3 –TEMPO–H 2 O–Bu 4 NHSO 4 reagent system in CH 2 Cl 2 . Intrigued by these results and in continuation of our efforts for the functionalization of glycals, we considered it worth developing reaction conditions that could lead to higher yields of such enones. Herein, we report our findings for efficient and mild reaction conditions for the oxidation of 3- O -benzylated (as well as 3- O -silylated) glycals to the corresponding 2,3-dihydro-4 H -pyran-4-ones using PIFA–water as an oxidizing reagent system along with TEMPO as a catalyst.…”
mentioning
confidence: 87%
“…The reaction scope was explored by varying the substituents at the propargylic position and also on the arene unit (Scheme 48). Further experimental studies using 18 O-labeled DMSO revealed that the ketonic oxygen atom in the final product originates from dimethylsulfoxide. Zhu and his co-workers developed a highly efficient and simple route for the synthesis of three types of 2-aminofurans via the Pd-catalyzed cycloisomerization of polysubstituted homoallenyl amides 156, using hypervalent iodine(III)reagents as the oxidant [82].…”
Section: Miscellenousmentioning
confidence: 99%
“…Various scientific papers, book chapters, and review articles have been published on the chemistry of hypervalent iodine. [10][11][12][13][14][15][16][17][18]. The functionalization of carbonyl compounds [19,20], cyclization [21][22][23][24], oxidative rearrangements [25][26][27], alkene difunctionalizations [28][29][30][31], and atom-transfer reactions [32], in the presence of hypervalent iodine compounds as reagents or catalysts, is now well established.…”
Section: Introductionmentioning
confidence: 99%
“…We have had a long-standing interest in the functionalization of glycals and their application in the synthesis of a variety of carbohydrate derivatives . As a continued activity, we recently reported a one-step method for the conversion of glycals into a mixture of 1-azido-2-acetoxy sugars and 2-azido-1-acetoxy sugars upon treatment with phenyliodine diacetate (PIDA) and TMSN 3 in the presence of 30 mol % of TMSOTf, with the latter being the major products. However, since the formation of 2-azido sugars was accompanied by the formation of 1-azido-2-acetoxy sugars, we sought to develop a new protocol that selectively gives 2-azido-2-deoxysugars in one step.…”
mentioning
confidence: 99%
“…More recently, the formation of an azide radical is also proposed in the reaction of PIFA and TMSN 3 in other organic transformations . In view of these literature reports and our own experience (vide supra) of using such reagent combinations in glycal functionalizations, we decided to revisit the reaction of glycals and find an alternate route to introduce an azido moiety exclusively at C-2. We had anticipated that the azide radical, if formed, would add on to glycals at C-2, generating a radical at the anomeric center which could either (i) react with another azide radical to give a 1,2-diazide or (ii) undergo oxidation with PIFA, leading to an oxonium ion, which can be trapped by a nucleophile to give the corresponding 2-azido-2-deoxyglycosides.…”
mentioning
confidence: 99%